Ethanol sensing properties of Zn2TiO4 particles - Santhaveesuk,T. (Elsevier Limited, 2015)
© 2015 Elsevier Ltd and Techna Group S.r.l. Zn2TiO4 particles were prepared using the ball-milling technique in ethanol solution. Zn powder mixing with anatase-TiO2 powder at ratio of 2:1 by mole were used as raw materials. The mixed powders were grounded in agate mortar for 2h, subsequently transferred into the ball-milled container with 1mm zirconia balls and, then, milled for 24h with ball-milling speeds of 200, 300 and 400rpm. The ratio of powders and zirconia balls was 1:20 by weight. After that, the powders were washed using distilled water for 4 times, dried at 80°C for 24h and calcined at 1000°C for 6h. Morphological characteristics, chemical compositions, phase formation and defect of the synthesized powder were examined. The SEM result showed that the particle size was reduced as increase in the ball-milling speed, while the EDS showed that the Zn/Ti ratio was about 2. The XRD indicated that the synthesized powders exhibited a face center cubic Zn2TiO4 phase, confirming by the Raman spectra. The Zn2TiO4 particles were fabricated as the thick film ethanol sensor and tested under 50 and 200ppm ethanol concentration at 300-500°C. Our results suggest that the Zn2TiO4 particles can be used for detection of ethanol vapor, and the sensor current increased with increasing of ethanol concentration. The highest sensitivity observed at 500°C was 3.83 for 200rpm, 1.92 for 300rpm and 2.36 for 400rpm samples. This implied that, the Zn2TiO4 sensor can be a good candidate for high temperature application.